The impact of headmaster distributive leadership towards professional learning communities - Siti Noor Ismail; Mohd Norakmar Omar; Shabinar Abd Halim; Ahmad Faizuddin; Mohan Rathakrishnan (Institute of Advanced Engineering and Science, 2022)
Effective school leadership has a massive impact on excellence and success. This study was conducted to identify distributive leadership and professional learning communities (PLC) practice in cluster primary schools of excellence (CPSE) in Kedah, Malaysia. This study also aimed to analyze the extent of principals’ distributive leadership influencing PLC practices and examine the relationship between these two variables. A total of 162 respondents from randomly selected five primary schools participated in the survey. The findings showed that the level of distributive leadership (M=4.4, SD=0.4) and teacher PLC practice (M=4.3, SD=0.4) were very high. The findings also showed a strong and significant positive relationship between principals’ distributive leadership and teachers’ PLC practice (r=.72). Furthermore, the findings indicated the existence of a strong influence for all dimensions of distributive leadership on PLC practices (r2=.60, p<.05). The findings of this study can be used as an essential guide in improving skills, adding knowledge of leadership management, and enhancing PLC practices in producing positive work culture towards realizing educational excellence.